PENGARUH EFEKTIVITAS OTOMATISASI, SISTEM KONTROL TENAGA PENJUAL DAN KEPUASAN ATAS WILAYAH PENJUALAN TERHADAP KINERJA TENAGA PENJUAL UNTUK MENINGKATKAN EFEKTIVITAS PENJUALAN ORGANISASI ( Studi Pada Perusahaan Distributor Farmasi Kotamadya Banjarmasin ) - Yansen Sianturi; Muhammad Riza Firdaus; Ikhwan Faisal (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
This study analyzed the effectiveness of automation factors, system control of sales and satisfaction of sales area which affect the sales’ performance to sales’ organization effectiveness (large pharmacy) in Banjarmasin. The sampling technique was divided into three phases, namely stratified, proportional, and purposive sampling. There were 120 subjects involved in the study. They are the head of branch, sales supervisors, sales personnel from pharmaceutical distribution company whose products are categorized as medicinal products and consumer goods. The analysis for the study used Structural Equation Model (SEM) in AMOS 20 program. The results of data analysis shows that the study supports five hypotheses and rejects two other hypotheses. The study also confirms a statistically significant relationship of the effectiveness of automation, system control of sales and satisfaction of sales area to the sales’ performance, as well as significant influence of sales’ performance and system control of sales to the effectiveness of sales’ organization. In addition, it is statistically found that the effectiveness of sales automation and satisfaction of sales area do not affect the sales’ organization effectiveness. The implication of this research to prepare personal in charge as coordinator of sales automation effectiveness and key performance indicator as guidance to measure the control which has been done and the discussion of sales territory alignment between sales supervisor and sales force.